University Size and Sustainability Disclosure in Indonesian Public Universities: Evidence from Sustainability Accounting and ESG Perspectives - Nur Wahyu Ningsih; Sudrajat (Al-Makki Publisher, 2026)
This research investigates the effect of university size on sustainability disclosure among Indonesian public universities. Sustainability disclosure has become increasingly important, as higher education institutions are expected to demonstrate accountability regarding environmental, social, and governance (ESG) performance. Despite growing international attention to sustainability reporting, disclosure practices among Indonesian public universities remain limited. Drawing on Legitimacy Theory and Resource-Based View Theory, this research argues that larger universities possess greater organizational resources, broader stakeholder exposure, and stronger legitimacy pressures that encourage sustainability disclosure. Using panel data from 22 Indonesian public universities from 2020 to 2024, university size is measured by the total number of enrolled students, while sustainability disclosure is assessed using the Campus Sustainability Assessment Tool (CSAT). The findings are expected to demonstrate that university size positively influences sustainability disclosure. This study contributes to the sustainability accounting literature by extending the determinants of sustainability disclosure from corporate settings to higher education institutions and highlighting the importance of institutional capacity in promoting ESG accountability. The findings also provide practical implications for university leaders to strengthen sustainability reporting systems as institutional scale expands and for policymakers to develop national sustainability reporting guidelines specifically designed for higher education institutions.